Aqueous organic flow battery containing N heterocyclic aromatic compound
By using N-containing heterocyclic aromatic compounds as the positive electrode electrolyte in an aqueous organic flow battery, the problem of poor electrochemical stability is solved, and the battery is high cycle stability and low-cost production is achieved.
Patent Information
- Application Number
- CN202311240256.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-25
AI Technical Summary
Among the existing water-based organic liquid flow batteries, the electrochemical stability is poor, and side reactions are prone to occur, resulting in the attenuation of the battery capacity.
An N-containing heterocyclic aromatic compound is used as the positive electrode electrolyte to improve redox reversibility and electrochemical stability by adjusting its structure and concentration.
It significantly improves the circulation stability of the flow battery, extends the battery life, and reduces production costs.
Smart Images

Figure CN119695218A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of liquid flow batteries, and specifically relates to an organic liquid flow battery. Background Art
[0002] With the reform of energy structure, building a clean, low-carbon, safe and efficient energy system has become an inevitable trend. The proportion of renewable energy such as wind power and solar energy in the energy structure has gradually increased, but these renewable energy sources are discontinuous, unstable and uncontrollable. Large-scale integration into the power grid will affect the stability of the power system. Therefore, advanced large-scale energy storage technology is needed to effectively store new energy power generation, smooth power output, participate in amplitude and frequency modulation, and achieve peak shaving and valley filling. Among them, liquid flow batteries have good application prospects in the field of large-scale energy storage because of the characteristics of independent design of output power and energy storage capacity, good safety, long cycle life, and environmental friendliness throughout the life cycle.
[0003] Among them, aqueous organic flow batteries mainly use water-soluble organic molecules as electrochemically active substances. Organic molecules have a wide range of sources and are mainly composed of carbon, hydrogen, oxygen, nitrogen and other elements that are abundant in nature. The most important thing is that the solubility, redox potential and stability of organic active molecules can be adjusted through molecular engineering modification and electrolyte regulation. In recent years, many organic active molecules have been reported to be used in aqueous organic flow batteries, such as quinones, viologens, TEMPOs, ferrocenes, and heterocyclic aromatic compounds. However, most of the organic molecules reported so far have poor electrochemical stability and are prone to side reactions that cause battery capacity decay.
[0004] In summary, it is very important to develop highly stable active organic molecules that can be used in aqueous organic flow batteries. Summary of the invention
[0005] The invention provides an aqueous organic liquid flow battery containing N heterocyclic aromatic compounds, and the liquid flow battery has the characteristic of good cycle stability.
[0006] In order to achieve the above object, the specific technical scheme of the present invention is as follows:
[0007] The present invention provides an organic liquid flow battery, comprising a single cell or a battery stack composed of more than two single cells; the single cell comprises a positive electrode, a diaphragm, and a negative electrode, the positive electrode electrolyte is passed into the positive electrode, or between the positive electrode and the diaphragm, and the negative electrode electrolyte is passed into the negative electrode, or between the negative electrode and the diaphragm; the positive electrode electrolyte in the positive electrode electrolyte is a N-containing heterocyclic aromatic compound.
[0008] In the liquid flow battery, the general structural formula of the N-containing heterocyclic aromatic compound is as follows:
[0009]
[0010] In formula (1), X can be independently selected from N, NH; Y can be independently selected from O, S, O + , or S + ;
[0011] Dashed lines are chemical bonds or do not exist;
[0012] n1 and n2 are selected from: 0, 1, 2, 3, 4;
[0013] m1 and m2 are selected from: 0, 1, 2, 3, 4;
[0014] Each R independently represents: -H, -F, -Cl, -Br, -CN, -NH2, -N(CH3)2, -N(CH3)3 + , -OH, -SH, -OCH3, -CH3, -SiH3, -CHO, -CF3, -COOH, -COOCH3, -CONH2, -SO3H, -NO2, -PO3H2, -R (alkyl chain);
[0015] Rf are independently functional groups: hydroxyl or in:
[0016] Ra and Rb may be the same or different and may be independently selected from -H, C1-C10 alkyl, -(CH2) n OH, -(CH2) n NH2, -(CH2) n N(CH3)2, -(CH2) n N(CH3)3 + 、-(CH2) n COOH, -(CH2) n SO3H, -(CH2) n PO3H2, or Ra and Rb together form a substituted or unsubstituted 3-8 membered nitrogen-containing heterocyclic ring or nitrogen-containing heteroaromatic ring, preferably containing N, O or two N, and the substituent is a C1-C4 alkyl group, wherein:
[0017] n is a natural number ranging from 1 to 10.
[0018] In the liquid flow battery, the concentration of the N-heterocyclic aromatic compound in the positive electrode electrolyte is 0.05-5 mol / L.
[0019] In the liquid flow battery, the positive electrode or negative electrode is carbon felt, carbon cloth, carbon paper, graphite plate, or metal plate respectively.
[0020] In the liquid flow battery, the negative electrode electrolyte in the negative electrode electrolyte of the liquid flow battery contains one or more of the following substances: vanadium dichloride, silicotungstic acid, stannous chloride, cadmium chloride, chromous chloride, lead sulfate, and titanium sulfate.
[0021] In the liquid flow battery, the total concentration of the negative electrode electrolyte in the negative electrode electrolyte is a solution ranging from 0.05 mol / L to its saturation concentration.
[0022] In the liquid flow battery, the diaphragm is an ion exchange membrane or a porous membrane.
[0023] The liquid flow battery, the positive electrode electrolyte and the negative electrode electrolyte also include a supporting electrolyte, the supporting electrolyte includes one or more of hydrochloric acid, sulfuric acid, perchloric acid, phosphoric acid, acetic acid, methanesulfonic acid, and trifluoromethanesulfonic acid, and the concentration of the supporting electrolyte is 0.05 mol / L to 6 mol / L; the solvent is water.
[0024] The N-containing heterocyclic aromatic compound disclosed in the present invention has excellent redox reversibility and electrochemical stability. When applied to aqueous organic liquid flow batteries, it exhibits excellent cycle stability and is a very promising class of positive electrode active molecules.
[0025] Beneficial effects of the present invention:
[0026] The present invention provides an organic liquid flow battery, which uses a N-containing heterocyclic aromatic compound as the positive electrode electrolyte of the liquid flow battery, which can undergo a reversible redox reaction and has good electrochemical reversibility and stability. In particular, in an acidic supporting electrolyte, the N-containing heterocyclic aromatic compound has a relatively positive redox potential, and the organic liquid flow battery obtained by matching with a suitable negative electrode electrolyte has excellent cycle stability. In addition, the N-containing heterocyclic aromatic compound is mainly composed of elements such as carbon, hydrogen, oxygen, nitrogen, and sulfur, and has a wide range of sources. Therefore, after large-scale production and manufacturing, the cost of the organic liquid flow battery containing N-heterocyclic aromatic compounds is greatly reduced compared to heavy metal ion liquid flow batteries such as vanadium, and can be used in the field of large-scale energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 For compound 1 1 H NMR spectra;
[0028] Figure 2 is the cyclic voltammogram of compound 1 in 3M H2SO4 solution;
[0029] Figure 3 For compound 2 1 H NMR spectra;
[0030] Figure 4 is the cyclic voltammogram of compound 2 in 3M H2SO4 solution;
[0031] Figure 5 For compound 3 1 H NMR spectra;
[0032] Figure 6 is the cyclic voltammogram of compound 3 in 3M H2SO4 solution;
[0033] Figure 7 For compound 4 1 H NMR spectra;
[0034] Figure 8 is the cyclic voltammogram of compound 4 in 3M H2SO4 solution;
[0035] Fig. 9 For compound 5 1 H NMR spectra;
[0036] Fig.10 is the cyclic voltammogram of compound 5 in 3M H2SO4 solution;
[0037] Fig.11 For compound 6 1 H NMR spectra;
[0038] Fig.12 is the cyclic voltammogram of compound 6 in 3M H2SO4 solution;
[0039] Fig.13 For compound 7 1 H NMR spectra;
[0040] Fig.14 is the cyclic voltammogram of compound 7 in 3M H2SO4 solution;
[0041] Fig.15 For compound 8 1 H NMR spectra;
[0042] Fig.16 is the cyclic voltammogram of compound 8 in 3M H2SO4 solution;
[0043] Fig.17 For compound 9 1 H NMR spectra;
[0044] Fig.18 is the cyclic voltammogram of compound 9 in 3M H2SO4 solution;
[0045] Fig.19 Cyclic voltammograms of toluidine blue (hereinafter referred to as TB) in 3M H2SO4 solution, with scan rates of 10mV / s, 20mV / s, 50mV / s, 100mV / s, and 200mV / s;
[0046] Fig. 20 Cyclic voltammograms of TB in 3M H2SO4 solution at different cycle numbers;
[0047] Fig.21 The cyclic voltammogram of brilliant cresyl blue in 3M H2SO4 solution, the scanning rates are 10mV / s, 20mV / s, 50mV / s, 100mV / s, 200mV / s;
[0048] Fig. 22 Graph showing the efficiency and discharge capacity of the assembled battery in Example 12 of the present invention under different current density charging and discharging conditions;
[0049] Fig.23 1 is the charge and discharge curve of the assembled battery at different current densities in Example 12 of the present invention;
[0050] Fig.24 The assembled battery in Example 12 of the present invention is at 80 mA / cm 2 Cycling performance diagram at different current densities.
[0051] Specific implementation methods
[0052] Example 1
[0053] Weigh phenothiazine (1g, 5mmol, purchased from Shanghai Aladdin Biochemical Co., Ltd.) and dissolve it in 50mL of glacial acetic acid, add a mixed solution of bromine (0.64mL, 12.6mmol) and glacial acetic acid (3ml), react at room temperature for 2.5 hours, add 200ml of ice-water mixture to precipitate, filter and collect the filter cake, wash the filter cake with water and ether in turn to obtain a crude product. Further purify with a silica gel column and recrystallize in acetone to obtain green crystals with a yield of 74%. 1 H NMR ( Figure 1 ) and liquid chromatography-high-resolution time-of-flight mass spectrometry analysis confirmed the molecular structure of the target product, compound 1.
[0054]
[0055] The redox behavior was studied by cyclic voltammetry. Compound 1 was weighed and dissolved in 10 ml of 3 mol / L sulfuric acid solution, and stirred to form a uniform solution to a 1 mmol / L solution. The prepared electrolyte was subjected to cyclic voltammetry test using a three-electrode system, with silver / silver chloride as the reference electrode, platinum electrode as the counter electrode, and glassy carbon electrode as the working electrode. The scan rate was 50 mV / s and the scan voltage range was 0.1-1.2 V.
[0056] like Figure 2 As shown, compound 1 has a pair of redox peaks at 0.9 V vs. SHE, but the reversibility is poor.
[0057] Example 2
[0058] Weigh phenothiazine (1g, 5mmol, purchased from Shanghai Aladdin Biochemical Co., Ltd.) and dissolve it in 5mL of glacial acetic acid. Add a mixed solution of nitric acid (2.55mL, 40mmol) and glacial acetic acid (6ml) dropwise. React at 35°C for 48 hours under an inert atmosphere (nitrogen). After cooling to room temperature, add 200ml of ice-water mixture, filter and collect the filter cake, wash the filter cake with water and ethanol in turn, and vacuum dry to obtain a yellow powder with a yield of 68%. 1 H NMR ( Figure 3 ) and liquid chromatography-high-resolution time-of-flight mass spectrometry analysis confirmed the molecular structure of the target product, compound 2.
[0059]
[0060] The redox behavior was studied by cyclic voltammetry. Compound 2 was weighed and dissolved in 10 ml of 3 mol / L sulfuric acid solution, and stirred to form a uniform solution to a 1 mmol / L solution. The prepared electrolyte was subjected to cyclic voltammetry test using a three-electrode system, with silver / silver chloride as the reference electrode, platinum electrode as the counter electrode, and glassy carbon electrode as the working electrode. The scan rate was 50 mV / s and the scan voltage range was 0.2-1.0 V.
[0061] like Figure 4 As shown, compound 2 has almost no redox peak in the potential range of 0.2-1.0V.
[0062] Example 3
[0063] Weigh 3,7-dinitrophenothiazine (0.5 g, 1.7 mmol) and SnCl2·2H2O (5.66 g, 25.5 mmol) and dissolve in 30 mL of ethanol. Reflux for 5 hours under an inert atmosphere. Cool to room temperature and add ice water. Adjust pH to 7 with 5% sodium bicarbonate solution. Extract with ethyl acetate (3×50 ml). Wash the organic layer with brine and dry with anhydrous sodium sulfate. Add 50 ml of petroleum ether when the remaining 5 ml of ethyl acetate is concentrated. Filter and collect the filter cake. Dry in vacuo to obtain a blue powder with a yield of 24%. 1 HNMR Figure 5 ) and liquid chromatography-high-resolution time-of-flight mass spectrometry analysis confirmed the molecular structure of the target product, compound 3.
[0064]
[0065] The redox behavior was studied by cyclic voltammetry. Compound 3 was weighed and dissolved in 10 ml of 3 mol / L sulfuric acid solution, and stirred to form a uniform solution to a 1 mmol / L solution. The prepared electrolyte was subjected to cyclic voltammetry test using a three-electrode system, with silver / silver chloride as the reference electrode, platinum electrode as the counter electrode, and glassy carbon electrode as the working electrode. The scan rate was 50 mV / s and the scan voltage range was 0.2-0.8 V.
[0066] like Figure 6 As shown, compound 3 has a pair of reversible redox peaks at 0.58 V vs. SHE, and the redox peak potential difference is ~35 mV, indicating that two electron transfer reactions occurred.
[0067] Example 4
[0068] Weigh 3-hydroxydiphenylamine (1g, 5.4mmol, purchased from Anhui Zesheng Technology Co., Ltd.), S (0.345g, 10.8mmol), I2 (0.041g, 0.162mmol) in a bottle, add 1,2-dichlorobenzene (7ml), react at 180℃ under inert gas atmosphere for 4 hours, cool to room temperature, and separate and purify with silica gel column to obtain pink powder with a yield of 68%. 1 H NMR ( Figure 7 ) and liquid chromatography-high-resolution time-of-flight mass spectrometry analysis confirmed the molecular structure of the target product, compound 4.
[0069]
[0070] The redox behavior was studied by cyclic voltammetry. Compound 4 was weighed and dissolved in 10 ml of 3 mol / L sulfuric acid solution, and stirred to form a uniform solution to a 1 mmol / L solution. The prepared electrolyte was subjected to cyclic voltammetry test using a three-electrode system, with silver / silver chloride as the reference electrode, platinum electrode as the counter electrode, and glassy carbon electrode as the working electrode. The scan rate was 50 mV / s and the scan voltage range was 0.1-1.0 V.
[0071] like Figure 8 As shown, compound 4 has two pairs of reversible redox peaks, indicating that it can undergo a two-step single-electron redox reaction. The first step redox potential is 0.43 V vs. SHE, and the second step potential is 0.71 V vs. SHE.
[0072] Example 5
[0073] Weigh 3-bromo-2-chloroaniline (0.5 g, 2.42 mmol, purchased from Anhui Zesheng Technology Co., Ltd.), CuI (0.138 g, 0.726 mmol), K2CO3 (1.672 g, 12.1 mmol) in a bottle, add 2-aminobenzenethiol (0.28 ml, 2.66 mmol, purchased from Anhui Zesheng Technology Co., Ltd.) and DMSO (5 ml), react at 120 ° C under an inert atmosphere for 48 hours, cool to room temperature, dilute the reaction mixture with ethyl acetate, and wash with water. Extract with ethyl acetate three times. The organic layer is dried over anhydrous sodium sulfate and concentrated to obtain a crude product, which is separated and purified by a silica gel column to obtain an orange solid. By 1 H NMR ( Fig. 9 ) and liquid chromatography-high-resolution time-of-flight mass spectrometry analysis confirmed the molecular structure of the target product, compound 5.
[0074]
[0075] The redox behavior was studied by cyclic voltammetry. Compound 5 was weighed and dissolved in 10 ml of 3 mol / L sulfuric acid solution, and stirred to form a uniform solution to a 1 mmol / L solution. The prepared electrolyte was subjected to cyclic voltammetry test using a three-electrode system, with silver / silver chloride as the reference electrode, platinum electrode as the counter electrode, and glassy carbon electrode as the working electrode. The scan rate was 50 mV / s and the scan voltage range was 0.2-1.0 V.
[0076] like Fig.10 As shown, compound 5 has no obvious redox peak in the range of 0.2-1.0V.
[0077] Example 6
[0078] Weigh 3-bromo-4-iodoaniline (0.5g, 1.68mmol, purchased from Anhui Zesheng Technology Co., Ltd.), CuI (0.096g, 0.5mmol), K2CO3 (1.16g, 8.4mmol) into a bottle, add 2-aminobenzenethiol (0.2ml, 1.87mmol, purchased from Anhui Zesheng Technology Co., Ltd.) and DMSO (5ml), react at 120°C under an inert atmosphere for 48 hours, cool to room temperature, dilute the reaction mixture with ethyl acetate, and wash with water. Extract with ethyl acetate three times. Dry the organic layer with anhydrous sodium sulfate and concentrate to obtain a crude product, which is separated and purified by silica gel column to obtain a purple solid. By 1 H NMR ( Fig.11 ) and liquid chromatography-high-resolution time-of-flight mass spectrometry analysis confirmed the molecular structure of the target product, compound 6.
[0079]
[0080] The redox behavior was studied by cyclic voltammetry. Compound 6 was weighed and dissolved in 10 ml of 3 mol / L sulfuric acid solution, and stirred to form a uniform solution to a 1 mmol / L solution. The prepared electrolyte was subjected to cyclic voltammetry test using a three-electrode system, with silver / silver chloride as the reference electrode, platinum electrode as the counter electrode, and glassy carbon electrode as the working electrode. The scan rate was 50 mV / s and the scan voltage range was 0.2-1.0 V.
[0081] like Fig.12 As shown, compound 6 has no obvious redox peak in the range of 0.2-1.0V.
[0082] Example 7
[0083] Weigh 3-bromo-4-chloroaniline (0.5g, 2.42mmol, purchased from Anhui Zesheng Technology Co., Ltd.), CuI (0.138g, 0.726mmol), K2CO3 (1.672g, 12.1mmol) in a bottle, add 2-aminobenzenethiol (0.28ml, 2.66mmol, purchased from Anhui Zesheng Technology Co., Ltd.) and DMSO (5ml), react at 120°C under an inert atmosphere for 48 hours, cool to room temperature, dilute the reaction mixture with ethyl acetate, and wash with water. Extract with ethyl acetate three times. The organic layer is dried over anhydrous sodium sulfate and concentrated to obtain a crude product, which is separated and purified using a silica gel column to obtain an orange solid. By 1 H NMR ( Fig.13 ) and liquid chromatography-high-resolution time-of-flight mass spectrometry analysis confirmed the molecular structure of the target product, compound 7.
[0084]
[0085] The redox behavior was studied by cyclic voltammetry. Compound 7 was weighed and dissolved in 10 ml of 3 mol / L sulfuric acid solution, and stirred to form a uniform solution to a 1 mmol / L solution. The prepared electrolyte was subjected to cyclic voltammetry test using a three-electrode system, with silver / silver chloride as the reference electrode, platinum electrode as the counter electrode, and glassy carbon electrode as the working electrode. The scan rate was 50 mV / s and the scan voltage range was 0.2-1.0 V.
[0086] like Fig.14 As shown, compound 7 has two pairs of redox peaks, indicating that a two-step single-electron redox reaction occurred, and the redox potentials were 0.4 V and 0.6 V vs. SHE, respectively.
[0087] Example 8
[0088] Weigh 2-bromo-3-chloroaniline (0.5g, 2.42mmol, purchased from Anhui Zesheng Technology Co., Ltd.), CuI (0.138g, 0.726mmol), K2CO3 (1.672g, 12.1mmol) into a bottle, add 2-aminobenzenethiol (0.28ml, 2.66mmol, purchased from Anhui Zesheng Technology Co., Ltd.) and DMSO (5ml), react at 120°C under an inert atmosphere for 48 hours, cool to room temperature, dilute the reaction mixture with ethyl acetate, and wash with water. Extract with ethyl acetate three times. The organic layer is dried over anhydrous sodium sulfate and concentrated to obtain a crude product, which is separated and purified using a silica gel column to obtain a purple solid. By 1 H NMR ( Fig.15 ) and liquid chromatography-high-resolution time-of-flight mass spectrometry analysis confirmed the molecular structure of the target product, compound 8.
[0089]
[0090] The redox behavior was studied by cyclic voltammetry. 4-aminophenothiazine was weighed and dissolved in 10 ml of 3 mol / L sulfuric acid solution, and stirred and shaken until a uniform solution was formed to form a 1 mmol / L solution. The prepared electrolyte was subjected to cyclic voltammetry test using a three-electrode system, with silver / silver chloride as the reference electrode, platinum electrode as the counter electrode, glassy carbon electrode as the working electrode, scanning speed of 50 mV / s, and scanning voltage range of 0.2-1.0 V.
[0091] like Fig.16 As shown, compound 8 has no obvious redox peak in the range of 0.2-1.0 V vs. SHE.
[0092] Example 9
[0093] In air, take phenothiazine (2g, 10mmol, 1equiv, purchased from Shanghai Aladdin Biochemical Co., Ltd.) and dissolve it in 50mL dichloromethane, slowly add iodine (7.64g, 30mmol, 3equiv) and 200ml dichloromethane solution, stir well, and react at room temperature for 12 hours. After the reaction is completed, vacuum filter, wash the filter cake with dichloromethane, and dry to obtain oxidized phenothiazine.
[0094] Weigh oxidized phenothiazine (0.724 g, 1 mmol) in 30 ml of dichloromethane, slowly add dimethylamine (1 ml, 2 mmol, purchased from Anhui Zesheng Technology Co., Ltd.), react at room temperature overnight, filter, and vacuum dry to obtain a black product with a yield of 25%. 1 H NMR ( Fig.17 ) and liquid chromatography-high-resolution time-of-flight mass spectrometry analysis confirmed the molecular structure of the target product, compound 9.
[0095]
[0096] The redox behavior was studied by cyclic voltammetry. Compound 9 was weighed and dissolved in 10 ml of 3 mol / L sulfuric acid solution, and stirred to form a uniform solution to a 1 mmol / L solution. The prepared electrolyte was subjected to cyclic voltammetry test using a three-electrode system, with silver / silver chloride as the reference electrode, platinum electrode as the counter electrode, and glassy carbon electrode as the working electrode. The scan rate was 50 mV / s and the scan voltage range was 0.2-1.0 V.
[0097] like Fig.18 As shown, compound 9 has a pair of redox peaks at 0.62 V vs. SHE, indicating a redox reaction with two electron transfers.
[0098] Example 10
[0099] Weigh TB and dissolve it in 10 ml of 3 mol / L sulfuric acid solution, shake and stir until a uniform solution is formed to obtain a 10 mmol / L TB solution. The prepared electrolyte is subjected to cyclic voltammetry test using a three-electrode system, with silver / silver chloride as the reference electrode, platinum electrode as the counter electrode, and glassy carbon electrode as the working electrode. The scan rates are 10 mV / s, 20 mV / s, 50 mV / s, 100 mV / s, 200 mV / s, and the scan voltage range is 0.2-0.8 V.
[0100] Depend on Fig.19 From the cyclic voltammetry data, it can be seen that under acidic conditions, there is a pair of obvious reversible redox peaks with good electrochemical reversibility. The average redox potential of TB is above 0.5Vvs.SHE.
[0101] Depend on Fig. 20 The cyclic voltammetry data under different cycle numbers are available, and the cyclic voltammetry curves of the 1st, 500th and 1000th cycles are basically overlapped, indicating its good stability.
[0102] Embodiment 11
[0103] Weigh brilliant cresyl blue and dissolve it in 10 ml of 3 mol / L sulfuric acid solution, shake and stir until it forms a uniform solution to a 10 mmol / L solution. The prepared electrolyte is subjected to cyclic voltammetry test using a three-electrode system, in which silver / silver chloride is used as the reference electrode, platinum electrode is used as the counter electrode, and glassy carbon electrode is used as the working electrode. The scan rates are 10 mV / s, 20 mV / s, 50 mV / s, 100 mV / s, 200 mV / s, and the scan voltage range is 0.2-0.9 V.
[0104] Depend on Fig.21The cyclic voltammetry data show that under acidic conditions, there is an obvious reversible redox peak, its electrochemical reversibility is good, and the redox potential is above 0.5Vvs.SHE.
[0105] Example 12
[0106] Weigh TB and dissolve it in 10 ml of 3 mol / L sulfuric acid aqueous solution, shake and stir, and after it forms a uniform solution, a 0.3 mol / L TB solution is used as the positive electrolyte. Commercial vanadium (1.6MV(III) / V(IV)+3M H2SO4) electrolyte is used as the positive and negative electrolytes, and the battery is assembled in the order and position of graphite current collector-carbon felt electrode-ion conductive membrane PBI-graphite felt electrode-graphite current collector (electrode effective area 48cm 2 ), use a magnetic pump to drive the positive and negative electrolytes into the battery cavity, and after charging, take the negative electrode V (II) and dilute it to 0.8 mol / L as the negative electrolyte. Assemble the battery in the order and position of graphite current collector-carbon felt electrode-ion conductive membrane PBI-graphite felt electrode-graphite current collector (electrode effective area 9cm 2 ), use a peristaltic pump to drive the positive and negative electrolytes into the battery cavity for charging and discharging.
[0107] like Fig. 22 As shown, at 20, 40, 60, 80, 100 mA / cm 2 When charged and discharged at a current density of , the coulombic efficiency of the battery is 100%, and the voltage efficiency and energy efficiency are both maintained at a high level. Fig.23 As shown in Figure 2, the battery maintains a high capacity at different current densities. Fig.24 As shown, the flow battery is at 80 mA / cm 2 The battery was charged and discharged for a long time at a current density of 1000 cycles, and there was no obvious attenuation in efficiency and capacity after 1000 cycles.
Claims
1. An aqueous organic liquid flow battery containing N-heterocyclic aromatic compounds, comprising a positive electrode electrolyte: characterized in that: The positive electrode electrolyte in the positive electrode electrolyte solution is one or more of the N-containing heterocyclic aromatic compounds; The general structural formula of the N-containing heterocyclic aromatic compound is as follows: In formula (1), X can be independently selected from one or both of N and NH; Y can be independently selected from O, S, O + , or S + When Y is selected from O + or S + , anion is Cl - Dashed lines are chemical bonds or do not exist; n1 and n2 are independently selected from: 0, 1, 2, 3 or 4, representing the number of R on the left and right six-membered rings respectively; m1 and m2 are independently selected from: 0, 1, 2, 3 or 4, representing the number of Rf on the left and right six-membered rings respectively; The substituents R on the left and right six-membered rings are independently represented by: -H, -F, -Cl, -Br, -CN, -NH2, -N(CH3)2, -N(CH3)3 + , -OH, -SH, -OCH3, -CH3, -SiH3, -CHO, -CF3, -COOH, -COOCH3, -CONH2, -SO3H, -NO2, -PO3H2, one or more of -C1-C10 alkyl; The Rf on the left and right 6-membered rings are independently functional groups: hydroxyl or in: Ra and Rb may be the same or different and may be independently selected from -H, C1-C10 alkyl, -(CH2) n OH, -(CH2) n NH2, -(CH2) n N(CH3)2, -(CH2) n N(CH3)3 + 、-(CH2) n COOH, -(CH2) n SO3H, -(CH2) n One or more of PO3H2, or Ra and Rb on the same N together form a substituted or unsubstituted 3-8 membered nitrogen-containing heterocycle or nitrogen-containing heteroaromatic ring, preferably a heterocycle or heteroaromatic ring containing N, O or two N, and the substituents on the heterocycle or heteroaromatic ring are one or more of C1-C4 alkyl groups, wherein: n is a natural number, ranging from 1 to 10.
2. The flow battery according to claim 1, characterized in that: The concentration of the N-heterocyclic aromatic compound in the positive electrode electrolyte is 0.05-5 mol / L, preferably 0.05-2 mol / L.
3. The liquid flow battery according to claim 1, characterized in that: The liquid flow battery includes a single cell or a battery stack composed of more than two single cells; the single cell includes a positive electrode, a diaphragm, and a negative electrode arranged in sequence, the positive electrode electrolyte is passed into the positive electrode, and / or the area between the positive electrode and the diaphragm, and the negative electrode electrolyte is passed into the negative electrode, and / or the area between the negative electrode and the diaphragm: the positive electrode or negative electrode is one or more of carbon felt, carbon cloth, carbon paper, graphite plate or metal plate.
4. The flow battery according to claim 3, characterized in that: The negative electrode electrolyte in the negative electrode electrolyte of the liquid flow battery contains one or more of the following substances: vanadium dichloride, silicotungstic acid, stannous chloride, cadmium chloride, chromous chloride, lead sulfate, and titanium sulfate.
5. The liquid flow battery according to claim 1 or 3, characterized in that: The diaphragm is an ion exchange membrane or a porous membrane.
6. The liquid flow battery according to claim 1, 3 or 4, characterized in that: The positive and negative electrolytes of the flow battery contain supporting electrolytes, which include one or more of hydrochloric acid, sulfuric acid, perchloric acid, phosphoric acid, acetic acid, methanesulfonic acid, and trifluoromethanesulfonic acid; the concentration of the supporting electrolyte is 0.05 to 6 mol / L; and the solvent is water.
Citation Information
Patent Citations
Inexpensive metal-free organic redox flow battery (ORBAT) for grid-scale storage
CN105409045A
Alkaline zinc-iron flow battery
CN108461784A
Aqueous neutral organic flow battery
CN111244518A
Aqueous all-organic mixed flow battery based on conjugated microporous polymer negative electrode containing redox active side group unit
CN112490477A
Ion exchange liquid membrane flow battery
CN116137339A